Wound Healing in Butterfly Pupal Wing Tissues: Real-Time In Vivo Imaging of Long-Range Cell Migration, Cluster Formation, and Calcium Oscillations - Shuka Nagai; Joji M. Otaki (Insects)
Insects can repair wounds and regenerate body parts in response to physical damage. Wound healing in butterfly pupal wing tissues is developmentally interesting because ectopic color patterns develop during healing, suggesting that normal and damage-induced color patterns may use similar mechanisms. Here we physiologically investigated wound healing and ectopic color pattern formation in butterfly pupal wing tissues using the blue pansy butterfly Junonia orithya. In response to physical puncture damage, various ectopic color patterns are formed around the damage site. After the wounding operation, we observed hemocytes migrating over long distances along the wing veins (lacunae) toward the damage site, where hemocytes and epidermal cells formed cellular clusters. Calcium oscillations were observed in cells at and near the damage site. Calcium oscillations were transiently affected by ruthenium red, an inhibitor of calcium transporters and channels, and ruthenium red caused various abnormalities in the scales of adult wings. These results suggest that cell migration, cluster formation, and calcium oscillations play important roles in wound healing and scale development at and near the damage site. Ectopic color patterns may develop in response to local calcium oscillations as a consequence of the evolutionary co-option of the healing process for normal development.